EVALUATION OF ISLAMIC BOARDING SCHOOL (IBS) DEVELOPMENT STRATEGY AS AGRIBUSINESS CENTER IN COMMUNITY EMPOWERMENT: Studi Kasus di Pondok Pesantren Nurul Qornain Jember - Villatus Sholikhah; Abdul Rokhim (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2020)
This study aims to explain the evaluation of the strategy for developing pesantren as an agribusiness center at the Nurul Qornain Islamic Boarding School Jember. This research approach uses a qualitative approach and the type of case study research. In this study, the informant determination technique used in this study was the Porposive Sampling technique. Data collection techniques using observation, interviews and documentation. The data analysis refers to the Miles and Huberman model, namely: data reduction, data presentation and drawing conclusions, both temporary conclusions, then verified and final conclusions. The validity test of the data used in this study, namely the credibility of the data (extension of participation, persistence of observation, triangulation, peer examination through discussion, and member checking). The results showed that the Nurul Qornain Islamic Boarding School carried out a process of monitoring or supervision (process evaluation) both directly and indirectly and evaluating the results which was carried out in two stages, namely the Post-harvest Accountability Report (LPJ) and the evaluation was carried out at the end of the school year or mid year.